How does mHealth benefit older Chinese adults’ quality of life? Examining the roles of eHealth literacy, health motivation, and patient activation - Sha Sarah Qiu; Jizhou Francis Ye; Fei You; Muhan Liu; Xinshu Zhao (Digital Health)
Background China is experiencing a rapid increase in its aging population, leading to the emergence of significant challenges to improve the quality of life (QoL) of older adults. The study aims to explore the potential benefits of using mobile health technology in improving the QoL for older Chinese adults. Method This study utilized a subsample of adults aged 60 and above from a cross-sectional, population-based national survey conducted among Chinese adults (N = 852). A moderated mediation analysis was conducted to investigate the impact of mHealth use on older Chinese adults’ QoL, focusing on the mediating roles of eHealth literacy and patient activation and the moderating effect of motivation for health promotion and prevention. Result The results indicate that mHealth use directly enhances the QoL of older Chinese adults (β = .061, p  < .001), and this effect is mediated by eHealth literacy and patient activation (β = .057, Boots 95% CI [.044, .072]). Furthermore, motivation for health promotion and prevention moderates the relationship between eHealth literacy and patient activation (β = .133, p  < .001). Conclusion These results demonstrate the positive impact of mHealth use on the QoL of older Chinese adults and reveal the underlying mechanisms involving mental and physical factors. These findings underscore the significance of increased attention to promoting mHealth use among older Chinese adults and provide a new way to enhance eHealth literacy and patient activation by encouraging the adoption of mHealth products.